Chiral Recognition of Carboxylates—Receptors, Analytical Tools, and More. Issue 6 (29th April 2016) - Ulatowski, Filip; Jurczak, Janusz
Abstract: Most carboxylic acids, which are among the most common molecules in biological systems, are chiral. The enantiomers of these species are commonly distinguished in nature, but such recognition has proven quite difficult to reproduce by using artificial receptors. Better knowledge of the chiral recognition of carboxylates is therefore crucial for a full understanding of host–guest phenomena in nature, and also for the design of new analytical devices. In this Focus Review we summarize and discuss the methods employed to evaluate receptors, and present a variety of structural designs that have been utilized in chiral receptors. Some advanced functions of receptors in sensors and sensor arrays are also reviewed. Abstract : Which side of the mirror? This Focus Review highlights recent achievements in chiral recognition of cabroxylates. Analytical methods are critically revised and various approaches to receptors structures are presented. Several examples of highly selective sensors or sensor arrays are shown to indicate possible future progress in the field.